The influence of dietary patterns, motor coordination, and physical activity on physical education outcomes among elementary school students - Yogi Satria Pratama; Wilda Welis; Anton Komaini; Sepriadi Sepriadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to analyze the direct and indirect effects of dietary patterns, physical activity, and motor coordination on Physical Education learning outcomes among elementary school students. This research employed a quantitative approach using path analysis involving 60 fourth-grade students selected through purposive sampling. Data were collected using the Food Frequency Questionnaire (FFQ), Physical Activity Questionnaire for Older Children (PAQ-C), motor coordination tests, and Physical Education report scores. Data analysis was conducted using SPSS 26 through descriptive statistics, classical assumption tests, regression analysis, and path analysis. The results showed that physical activity had the strongest effect on learning outcomes (β = 0.409; p < 0.001), followed by motor coordination (β = 0.378; p < 0.001) and dietary patterns (β = 0.200; p = 0.041). Simultaneously, the variables explained 58.8% of the variance in learning outcomes (R² = 0.588). Furthermore, dietary patterns and physical activity significantly influenced motor coordination (p = 0.001). These findings indicate that healthy lifestyles and motor competence contribute substantially to improving students’ Physical Education achievement.